Queer Literary Assemblages: Justin Torres's Blackouts (2023). - Hueso-Vasallo, Manuel (Taylor & Francis, 2024)
This essay aims to explore the connection between assemblage theory and queer studies, arguing that this connection could be extremely productive as a critical tool through which to explore literary texts dealing with lesbian, gay, bisexual, transgender, queer, and other sexual and gender minorities (hi)stories. Although assemblage theory was originally articulated by Giles Deleuze and Felix Guattari in Milles Plateaux, there has recently been, as the research project into which this essay is integrated demonstrates, a noticeable spike of interest regarding assembled thinking. This interest, however, seems to have overlooked the critical potential that combining assemblage theory and queer studies could offer. In this sense, this essay details the affinities shared between both fields of critical enquiry and, through the lenses of Bill Brown’s “Re-Assemblage (Theory, Practice, Mode),” analyses Justin Torres’s novel Blackouts, in order to provide a working example of how the combination of these affinities could lead to new understandings of queer literary modes. I shall argue that Torres’s novel is an important text from which to rethink the ways in which we analyze queer literature precisely due to its inclusion of assembled materials within its pages.
Keywords: Teoría queer; Torres, Justin (1980-) - Crítica e interpretación; Justin Torres; Bill Brown; Queer studies; Assemblage theory